Management of Dorsal Graft and Implant Infections - Chen, David S.; Wang, Tom D. (Facial Plastic Surgery, 2020)
Deficiency of the nasal dorsum can result from several etiologies, most commonly congenital, traumatic, or iatrogenic. The use of dorsal grafts or implants for augmentation of the dorsum is a mainstay of both functional and cosmetic rhinoplasty. Due to the cosmetically sensitive nature of the dorsum, and the relatively large amount of graft or implant material that is typically used, infections in this area can be particularly difficulty to manage. Here, we review the current literature on dorsal graft and implant infections, along with options for management.
Keywords: infected; nasal; implants